Enhancing Customer Loyalty in the Cosmetic Industry: The Role of Store Location and Service Quality - Nisa, Aviyatun; Indiani, Ni Luh Putu (Jurnal Ilmiah Manajemen & Bisnis, 2023)
In the midst of intense competition in the cosmetics industry, customer loyalty is an important key in maintaining the sustainability and existence of a company. This study aims to analyze the influence of store location and service quality on customer loyalty with customer satisfaction as a mediation variable. The investigation aims to understand the relationship between variables, the nature of mediation, and become a cornerstone in formulating practical implications for the cosmetic retail industry. The population in this study is all customers of the cosmetic industry in Badung Regency. The study obtained 150 valid samples. The data collection method is a survey method using questionnaires which was carried out offline and online through a link. The analysis technique used is an inferential analysis technique with Partial Least Square (PLS) to analyze relationships among latent constructs by modeling both the measurement and structural components of a theoretical model. The results showed that there is a significant relationship between store location and service quality to customer loyalty both directly and indirectly through customer satisfaction and this is a partial mediation, suggesting that there are other factors not included in the research model that could explain the relationship between store location and loyalty, as well as service quality and loyalty. The suggestion proposed to increase customer loyalty in cosmetic retail is to pay attention to the availability of parking lots, location convenience, and ease of accessing store locations. In addition, the quality of service can be improved through supporting facilities and infrastructure, the ability of marketers to welcome customers and provide a good value and experience to customers that can be done through trained employees.